Retrospective analysis of nystagmus characteristics and clinical applications of positional testing in patients with cupulolithiasis of the posterior semicircular canal in benign paroxysmal positional vertigo - Wu, Jing; Zou, Yihuai; Xu, Wenyan; Ma, Hongming; Huang, Lixian; Zhao, Bo; Sun, Liman (Frontiers in Neurology, 2024)
Objective This study aimed to investigate the characteristics of positional nystagmus in patients with cupulolithiasis of the posterior semicircular canal-benign paroxysmal positional vertigo (PC-BPPV-cu) to improve clinical diagnostic accuracy. Methods This study retrospectively analyzed 128 cases of PC-BPPV-cu and 128 cases of canalolithiasis of BPPV (PC-BPPV-ca). General data, intensity, distribution, and the correlation of positional nystagmus were compared between the two groups. Results Compared to the PC-BPPV-ca group, more cases from the PC-BPPV-cu group initially presented in the emergency department (P < 0.05). The most frequent positional nystagmus induced by PC-BPPV-cu was torsional-upbeat nystagmus, characterized by the upper pole of the affected eye beating toward the lower ear and vertically upward (387 cases, 59.7%). It was followed by torsional-downbeat nystagmus, characterized by the upper pole of the unaffected eye beating toward the lower ear and vertically downward (164 cases, 25.3%). The former represented posterior canal excitatory nystagmus (PC-EN), while the latter represented posterior canal inhibitory nystagmus (PC-IN). In the PC-BPPV-cu group, PC-EN was most easily caused by the Half Dix–Hallpike (HH) maneuver on the affected side, while PC-IN was most easily induced by a face-down position (FDP) on the unaffected side at approximately 45° angle (45° FDP). The vertical slow phase velocity (v-SPV) of positional nystagmus was more potent in the affected HH than in other positions with PC-EN (all P < 0.05); the v-SPV of positional nystagmus was greater in the 45° FDP than in different positions with PC-IN (all P < 0.05); the v-SPV of the affected Dix–Hallpike (DH) maneuver in the PC-BPPV-ca group was significantly greater than that of the affected HH maneuver in the PC-BPPV-cu group (P < 0.05). The a priori analysis showed that the strongest correlation with HH positional nystagmus was observed in the affected side roll test, followed by the DH maneuver. Conclusion In the PC-BPPV-cu group, the HH maneuver most easily induced PC-EN on the affected side, and PC-IN was most easily induced by the 45° FDP. In some cases of PC-BPPV-cu, significant nystagmus was not observed to be induced in the DH position on the affected side; however, vertical rotation nystagmus was induced in the roll-test position on the affected side. In such cases, PC-BPPV-cu diagnosis should be considered, and HH and 45° FDP tests should be conducted to support the diagnosis.